EFEKTIFITAS PROJECT BASED-LEARNING (PjBL) TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA KELAS X SMAN 2 SAPE - didi kuswara; Sri Setiawati (PENBIOS: JURNAL PENDIDIKAN BIOLOGI DAN SAINS, 2019)
This study aims to determine the application of project base learning (PjBL) to the critical thinking skills of class X students of SMAN 2 Sape. This research is a quase experiment with a non equivalent pretest posttest control group design. The population in this study were all students of class X and the samples of this study were class XA and XB using simple random sampling techniques. Class XA as a control class with group discussion techniques and class XB as an experimental class treated with Project-Based Learning. The research instrument used was a matter of critical thinking with pretest and posttest. The results showed that from the results of the analysis of the hypothesis test with a regression test obtained a significance value of critical thinking 0,000 less than 0.05 (0.00 <0.05), meaning that there was a significant effect of PjBL on students' critical thinking abilities. The conclusion from this study is that there is an effect of Project-Based learning on students' critical thinking skills.